Surface cracks—geomorphological indicators for late Quaternary halotectonic movements in Northern Germany - Hardt, Jacob; Norden, Ben; Bauer, Klaus; Toelle, Ole; Krambach, Jenny (2021)
Loading and unloading effects of the Scandinavian Ice Sheet triggered halotectonic movements in Northern Germany. We present newly detected geomorphological features—termed surface cracks—which indicate a relation between ice sheet-induced salt movement and surface processes. As a part of the Central European Basin System, numerous Zechstein salt structures are abundant in the North German Basin. On the basis of high-resolution digital terrain data, more than 160 surface cracks were mapped in Northern Germany, which were grouped into 30 clusters. Almost all of the surface cracks occur above the top regions of Zechstein salt structures. The surface cracks can be several kilometres long, up to more than 20 m deep and more than 100 m wide. The comparison of the shape of the salt structures and the orientation of the cracks reveals a geometric dependency, indicating that the cracks preferably occur near the crest margins of the salt structures. Furthermore, 3D seismic data from two sites show that subsurface faults originating from salt movement exist beneath the surface cracks. We interpret the cracks as surface ruptures due to ice sheet-induced halotectonic movements. The cracks occur in a variety of Quaternary sediments and landforms. This indicates that widespread halokinetic movements occurred in the region after the last (Weichselian) deglaciation and likely before the thawing of the permafrost, possibly in a time frame from c. 30–20 ka until c. 15 ka.